High‐Energy Nickel‐Cobalt‐Aluminium Oxide (NCA) Cells on Idle: Anode‐ versus Cathode‐Driven Side Reactions. Issue 6 (18th March 2021) - Zülke, Alana; Li, Yi; Keil, Peter; Burrell, Robert; Belaisch, Sacha; Nagarathinam, Mangayarkarasi; Mercer, Michael P.; Hoster, Harry E.
Abstract: We report on the first year of calendar ageing of commercial high‐energy 21700 lithium‐ion cells, varying over eight state of charge (SoC) and three temperature values. Lithium‐nickel‐cobalt‐aluminium oxide (NCA) and graphite with silicon suboxide (Gr‐SiO x ) form cathodes and anodes of those cells, respectively. Degradation is fastest for cells at 70–80 % SoC according to monthly electrochemical check‐up tests. Cells kept at 100 % SoC do not show the fastest capacity fade but develop internal short circuits for temperatures T ≥40 °C. Degradation is slowest for cells stored close to 0 % SoC at all temperatures. Rates of capacity fade and their temperature dependencies are distinctly different for SoC values below and above 60 %, respectively. Differential voltage analyses, apparent activation energy analysis, and endpoint slippage tracking provide useful insights into the degradation mechanisms and the respective roles of anode and cathode potential. We discuss how reversible losses of lithium might play a role in alleviating the rate of irreversible losses on commercial cells. Abstract : Idle power : NCA/Gr‐SiO x 21700 cells develop a spoon‐shaped profile of capacity fade as a function of state of charge (SoC) when idle. Cells at 100 % SoC have better capacity retention than cells stored at 80 or 90 % SoC but develop micro‐short circuits when exposed to T ≥40 °C. Our analysis supports the proposition of a cathode‐driven shuttle mechanism that alleviates loss of lithium to the (re)formation of the solid‐electrolyte interphase (SEI). Those are interesting observations given that this type of commercial battery is widely employed in electric cars, in which SoCs are generally kept at high levels by their users.